Impulsivity, Painful and Provocative Events, and Suicide Intent: Testing the Interpersonal Theory of Suicide. Issue 4 (11th October 2018) - Jordan, Joshua T.; Samuelson, Kristin W.; Tiet, Quyen Q.
Abstract : Objective: The Interpersonal Theory of Suicide (IPTS; Joiner, 2005. Why People Die by Suicide . Cambridge, MA: Harvard University Press) hypothesizes that repeated exposure to painful and provocative events (PPE) increases capability for suicide (CS), therefore facilitating the development of suicidal intent, and that impulsive individuals are more likely to experience these painful and provocative events, creating an indirect relationship between impulsivity and CS. Research to date largely supports this hypothesis but has not translated this theory to actual suicidal intent. Method: The present study used data from the MacArthur Violence Risk Assessment Study to examine the relationship between PPE and intent, and the indirect relationship between impulsivity and intent among a sample of 245 recent suicide attempters, using the clinician‐rated Suicide Intent Scale as an objective measure of intent. Results: Results supported the hypothesized direct relationship between PPE and intent, and the indirect relationship between impulsivity and intent through PPE. There was no direct relationship between impulsivity and intent, suggesting that the relationship between impulsivity and intent occurs entirely through exposure to PPE. Conclusions: These findings suggest that assessing exposure to painful and provocative events is critical in evaluating risk of suicide, and that impulsivity itself does not confer an increased risk of lethal or nearly lethal attempts.